From Superiority to Universalism: The Genealogical Transformation of Ummatan Wasaṭan in Egyptian Tafsīr Tradition - Robby Hidayatul Ilmi; Muhammad Hariyadi (Universitas Islam Negeri Imam Bonjol Padang, 2025)
The Qur’anic verse of Al-Baqarah [2]:143 has experienced considerable semantic evolution within the Egyptian exegetical tradition, transitioning from a representation of Muslim communal superiority in the classical era to a foundation for the discourse of wasatiyyah (moderate) Islam in the 21st century. This article investigates the genealogical shift by exploring interpretations of the phrase ummatan wasatan through five generations of Egyptian scholars: al-Suyūṭī (15th century), Muḥammad ʿAbduh (early 20th century), Muḥammad Muḥammad al-Madanī (mid-20th century), Muḥammad Mutawallī al-Shaʿrāwī (late 20th century), and Yūsuf al-Qaraḍāwī (21st century). By employing a qualitative-interpretive approach based on genealogical-hermeneutic and ideological analysis, the study outlines four phases of semantic development. Initially, during the classical era (al-Suyūṭī), the passage functioned as a doctrinal endorsement of the Muslim community's supremacy. Secondly, during Egypt's modernisation era (Abduh), it turned into a means for internal criticism against the ummah's stagnation. Thirdly, in the context of colonialism and contemporary ideological conflicts (al-Madanī and al-Shaʿrāwī), the verse was used as an ideological defence against Western influence and an epistemic foundation for establishing a manhaj wasaṭī (moderate methodology). And lastly, in the post-9/11 globalisation age (al-Qaraḍāwī), its meaning expanded to include a diplomatic-ethical concept reflecting tolerance, plurality, and interfaith cooperation within a global context. This study suggests that socio-political circumstances and the ideological orientations of its interpreters consistently influence Qur'anic exegesis. Therefore, the shift from theological exclusivity to ethical universalism exemplifies the dynamic interaction among sacred texts, social realities, and ideological interests within contemporary Islamic exegetical tradition.